Antinociceptive activity of Cnicus benedictus L. leaf extract: a mechanistic evaluation - Ahmadimoghaddam, Davoud; Sadeghian, Reihaneh; Ranjbar, Akram; Izadidastenaei, Zohreh; Mohammadi, Saeed (Research in pharmaceutical sciences, 2020)
Background and purpose: Cnicus benedictus, a medicinal herb, traditionally had been used for the treatment of stomachache pain. In this study, the possible efficacy of Cnicus benedictus leaf methanolic extract (CBHE) and also cnicin, one of its major constituents, was measured on pain. Experimental approach: In this study, pain assessment tests include writhing, tail-flick (TF), and formalin- induced paw licking test (FIPLT) were used. To understand the possible mediated anti-nociceptive mechanism of CBHE, the opioid mechanism(s), and involvement of the L-arginine/ nitric oxide/cGMP/ATP-sensitive potassium channel pathway (LNCaP) were scrutinized. Findings/Results: In TF and writhing tests, CBHE (150 and 300 mg/kg, i.p) remarkably exhibited an anti-nociceptive effect compared to that of the control. Furthermore, CBHE (150 and 300 mg/kg, i.p) in comparison with the control showed a noteworthy anti-nociceptive effect (P < 0.01) in the tonic phase of FIPLT. In the writhing test, administration of selective opioid antagonist (naltrindole, nor-binaltorphimine, and naloxonazine) attenuated the anti-nociceptive effect of CBHE (300 mg/kg) in comparison with control. Moreover, pre-treatment with Nω-nitro-L-arginine methyl ester hydrochloride, L-arginine hydrochloride, and glibenclamide significantly blocked the CBHE (300 mg/kg) anti-nociception (P < 0.05) while administration of sodium nitroprusside remarkably potentiated (P < 0.05) the antinociception induced by CBHE in the tonic phase of the FIPLT. Besides, cnicin (30 mg/kg) showed noteworthy anti-nociceptive effects in writhing, TF, and FIPLT paradigms. Conclusion and implications: Taken together, we elucidate that both CBHE and cnicin demonstrated antinociceptive effects in behavioral tests. The possible mechanisms of CBHE antinociception may involve in various neural signaling and modulatory pathways including LNCaP and opioidergic mechanisms.